2005
DOI: 10.1017/s0263574704001341
|View full text |Cite
|
Sign up to set email alerts
|

Using potential energy to measure work related activities for persons wearing upper limb prostheses

Abstract: This study presents a novel means of assessing upper limb tasks by using mechanical energy. Potential energy quantifies six work related activities, studied for 20 working-age non-prosthesis users and three powered below elbow prosthesis users. Two marker trajectories on each of the upper arms, forearms, and hands were captured using a 3-camera VICON 140™ system. Task and arm dominance of non-prosthesis users are highly significant ($p\,{<}\,0.01$) with arm dominance effects being more pronounced for prosthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…In contrast, ACMC assesses how the prosthesis is normally used to assist the sound hand to perform bimanual activities. It has been reported that prosthesis users prefer to be assessed in their usual way of using the prosthesis [47], and consistent results are observed if they are allowed to perform the activities in their usual way [43]. Both assessment procedures are useful for different purposes, and it is important for clinicians to be aware of the different assessment procedures before they evaluate their clients.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In contrast, ACMC assesses how the prosthesis is normally used to assist the sound hand to perform bimanual activities. It has been reported that prosthesis users prefer to be assessed in their usual way of using the prosthesis [47], and consistent results are observed if they are allowed to perform the activities in their usual way [43]. Both assessment procedures are useful for different purposes, and it is important for clinicians to be aware of the different assessment procedures before they evaluate their clients.…”
Section: Discussionmentioning
confidence: 94%
“…It is not easy to compare the MDC values of the ACMC and the AM-ULA because these two instruments are quite different in their assessment procedures. Although unilateral users rarely use the prosthesis to perform one-hand activities [43][44][45][46], the AM-ULA requests unilateral users to perform such activities with the prosthesis so that the assessment can be compared with the use of a sound limb and a ceiling effect is also avoided. In contrast, ACMC assesses how the prosthesis is normally used to assist the sound hand to perform bimanual activities.…”
Section: Discussionmentioning
confidence: 99%
“…CTD, or worn-limb syndrome, is frequently found in people with unilateral upper-limb loss [12,42]. Black et al found that 53 percent of unilateral upper-limb patients using a prosthetic device had pain in their remaining arm, most of which was associated with CTD [43]. CTD and overuse injuries are also estimated to be three times more likely in people with unilateral upperlimb loss than in the general workforce, in which CTD is also frequently reported [43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…Black et al found that 53 percent of unilateral upper-limb patients using a prosthetic device had pain in their remaining arm, most of which was associated with CTD [43]. CTD and overuse injuries are also estimated to be three times more likely in people with unilateral upperlimb loss than in the general workforce, in which CTD is also frequently reported [43][44][45][46][47]. In our study's two groups, CTD was significantly higher (60%) in the Vietnam group, who are 40 years from their limb loss, than in the OIF/OEF group (38%), who are 3 to 4 years from their limb loss.…”
Section: Discussionmentioning
confidence: 99%
“…Upperlimb motion analysis is not novel to the prosthetic population [16], but there is a lack of consensus in defining a standardized task or methodology to allow comparison and consistency across investigators. More recently, standardized methods for upper-limb functional tasks have been proposed by various authors [17][18][19] in order to define an upper-limb motion analysis protocol analogous to lowerlimb gait analysis.…”
Section: Introductionmentioning
confidence: 99%